Precarização do trabalho e saúde dos magistrados trabalhistas no Brasil (2003 - 2014) - Nogueira, Thayse Palmela [UNESP] (2015)
Our objective was to investigate the work of righteousness production conditions in Brazil and its impacts on the health of the labor judiciary from 2003 to 2014, a period that marks the beginning of the Constitutional Amendment number 45/2004, which caused significant changes in the Brazilian Judiciary in particular in the labor courts, which was expanded competence, through the new wording given to art.114 of the Federal Constitution. In these ten years of the judicial modernization, chatty modernization permeated by business logic, there was the introduction of informational-organizational technologies, in addition to the management shock, which is nothing but the electronic court case coupled to Toyotist management. In this transition process, the judges of first instance of the Labor Court failed to report the dimensions of the work precariousness and health through interviews and empirical data collection. With the data, we found that the profile of the labor judiciary in Brazil has been gradually changing face, a scenario that was predominantly male, is giving way to a process of feminization and juvenization that has expanded within the Justice, mainly in labor courts.